The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/bioengineering8030039
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Based Electrospun Materials for Tissue Engineering: A Systematic Review

Abstract: Collagen is a key component of the extracellular matrix (ECM) in organs and tissues throughout the body and is used for many tissue engineering applications. Electrospinning of collagen can produce scaffolds in a wide variety of shapes, fiber diameters and porosities to match that of the native ECM. This systematic review aims to pool data from available manuscripts on electrospun collagen and tissue engineering to provide insight into the connection between source material, solvent, crosslinking method and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 112 publications
(180 reference statements)
0
40
0
Order By: Relevance
“…The key obstacles to its development are related to weak mechanical properties and high degradation rates. Nevertheless, recent works [ 47 , 48 , 49 ] in tissue engineering demonstrate quite a good potential for the use of collagen-based composite fibers. In [ 24 ], the authors introduced the bacterial cellulose–collagen nanocomposites, and showed that the increase of bacterial cellulose content led to a better mechanical stability.…”
Section: Modern Polymer-based Fibrous Compositesmentioning
confidence: 99%
“…The key obstacles to its development are related to weak mechanical properties and high degradation rates. Nevertheless, recent works [ 47 , 48 , 49 ] in tissue engineering demonstrate quite a good potential for the use of collagen-based composite fibers. In [ 24 ], the authors introduced the bacterial cellulose–collagen nanocomposites, and showed that the increase of bacterial cellulose content led to a better mechanical stability.…”
Section: Modern Polymer-based Fibrous Compositesmentioning
confidence: 99%
“…Although several review papers have been published about biomedical applications of collagen, 10‐16 this manuscript presented a more comprehensive one that covers the developmental milestones of different types of collagen in biomedical engineering along with their sources, structures, and functional properties. Moreover, the current manuscript presents the broad applications of collagen in tissue engineering, skin substitutes, and wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The ECM composes a complex and accurately organized three‐dimensional network of biomolecules, including fibrous proteins and glycosaminoglycan‐based components. ECM is used frequently as a whole or as individual components in skin wound healing 5,6,24 . Fibrous elements such as collagens and fibronectin create the frame, stability, and tensile strength and regulate cell adhesion and migration 5,6,25 …”
Section: Introductionmentioning
confidence: 99%
“…3T3 fibroblast, cell adhesion, cell attachment, electrospun, extracellular matrix, plasma treatment, polycaprolactone frequently as a whole or as individual components in skin wound healing. 5,6,24 Fibrous elements such as collagens and fibronectin create the frame, stability, and tensile strength and regulate cell adhesion and migration. 5,6,25 The conditioning of hydrophobic synthetic scaffolds with cell-secreted ECM, rather than tissue ECM, has recently attracted attention to engineering biomimetic scaffolds.…”
Section: Introductionmentioning
confidence: 99%